2014
DOI: 10.1186/s13071-014-0490-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of zoonotic pathogens of free-ranging non-human primates from Zambia

Abstract: BackgroundWildlife may harbor infectious pathogens that are of zoonotic concern acting as a reservoir of diseases transmissible to humans and domestic animals. This is due to human-wildlife conflicts that have become more frequent and severe over recent decades, competition for the available natural habitats and resources leading to increased human encroachment on previously wild and uninhabited areas.MethodsA total of 88 spleen DNA samples from baboons and vervet monkeys from Zambia were tested for zoonotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…[22,26,27,28,43,44,45,46,47]; 13 reporting on Coxiella burnetii [23,24,25,39,40,41,48,49,50,51,52,53,54]; five on Mycobacterium bovis [42,55,56,57,58]; eight on Rickettsia spp. [25,53,54,59,60,61,62,63]; five reporting on Anaplasma spp. [53,63,64,65,66]; two each on Bartonella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22,26,27,28,43,44,45,46,47]; 13 reporting on Coxiella burnetii [23,24,25,39,40,41,48,49,50,51,52,53,54]; five on Mycobacterium bovis [42,55,56,57,58]; eight on Rickettsia spp. [25,53,54,59,60,61,62,63]; five reporting on Anaplasma spp. [53,63,64,65,66]; two each on Bartonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…[25,53,54,59,60,61,62,63]; five reporting on Anaplasma spp. [53,63,64,65,66]; two each on Bartonella spp. [67,68] and Borrelia spp.…”
Section: Resultsmentioning
confidence: 99%
“…Tamaki et al [23] reported 16.7% seroprevalence for antibodies against Rickettsia conorii in humans despite cross-reactivity of spotted fever group rickettsia and R. felis on serology having been documented [24], hence possibility of misdiagnosing some closely related species cannot be excluded. Later Nakayima et al [25] found molecular evidence of spotted fever group rickettsiae closely related to Rickettsia africae (the causative agent for African tick bite fever) in free-ranging non-human primates in Mambwe District near Luangwa National Park, Zambia. With the endemic cases of malaria [26] little attention has been given to other pathogens that cause febrile illness, hence possibilities of misdiagnosis could be high.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts have revealed more than 800 novel viruses and have contributed to an extensive database of zoonotic pathogens (Epstein and Anthony, 2017). Other studies have focused on diverse parasite types across hosts, including Chagas-like trypanosomes in bats (Dario et al, 2017), Babesia and Rickettsial pathogens in nonhuman primates (Nakayima et al, 2014), and pathogenic bacteria in urban mice (Williams et al, 2018).…”
Section: Host-specific Surveillance For Eidsmentioning
confidence: 99%